Metastable state preceding shear zone instability: Implications for earthquake-accelerated landslides and dynamic triggering - Yan Li; Wei Hu; Qiang Xu; Hui Luo; Chingshung Chang; Xiaoping Jia (Proceedings of the National Academy of Sciences, 2025)
Understanding the dynamic response of granular shear zones under cyclic loading is fundamental to elucidating the mechanisms triggering earthquake-induced landslides, with implications for broader fields such as seismology and granular physics. Existing prediction methods struggle to accurately predict many experimental and in situ landslide observations due to inadequate consideration of the underlying physical mechanisms. The mechanisms that influence landslide dynamic triggering, a transition from static (or extremely slow creeping) to rapid runout, remain elusive. Herein, we focus on the inherent physics of granular shear zones under dynamic loading using ring shear experiments. Except for coseismic slip caused by the dynamic load, varying magnitudes of postseismic creep with increasing cycles of dynamic loading are observed, highlighting the effects of coseismic weakening (shear zone fatigue) and subsequent postseismic healing. A metastable state, characterized by a significant increase in postseismic creep, typically precedes shear zone instability. The metastable state may arise as weakened shear resistance approaches the applied shear stress, demonstrating a phase transition from a solid-like state to a fluid state (plastic granular flow). The metastable state may potentially indicate the shear zone’s stress state and serve as a precursor to impending instability. Furthermore, the proposed mechanisms offer a compelling explanation for the widespread postseismic landslide movement following earthquakes. Incorporating these mechanisms into the Newmark method has the potential to improve the prediction of earthquake-induced landslide displacement and enhance our understanding of dynamic triggering.